THE REAL ORIGIN OF GLOBAL FINANCIAL IMBALANCES. (November 2013) - Wang, Xiaobing; Walters, Bernard; Lawson, David; Amann, Edmund
Abstract There is an evident global imbalance puzzle: debt levels in developed countries are continuing to expand despite their huge size whereas the size of foreign exchange reserves held by developing countries continues to grow. This paper argues that this pattern of global imbalances is a consequence of an asymmetric international system, the roots of which lie in the differences in labour structures between the developed and developing countries. It suggests that this global imbalance is likely to continue and is beneficial for both developed and developing countries. Copyright © 2013 John Wiley & Sons, Ltd.